Justice for Palestine: A Call to Action from Indigenous & Women of Color Feminists - The People's Forum NYC (2021)
We come together on the 10th anniversary of our last day in Palestine, hundreds of presentations, articles, panels, and interventions later, to offer our Report Card reaffirming the relevance and urgency of re-telling stories of apartheid, ethnic cleansing, and settler colonialism and of Palestinian steadfastness, resistance and resilience. SPEAKERS: Dr. Angela Davis Dr. Anna Guevarra Dr. Barbara Ransby Dr. Beverly Guy-Sheftall Dr. Chandra Talpade Mohanty Dr. Gina Dent Dr. G. Melissa Garcia Dr. Rabab Abdulhadi Dr. Waziyatawin Co-sponsored by Arab and Muslim Ethnicities and Diaspora Studies
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; asie; cours; discipline; féminisme autochtone; féminisme décolonial; féminisme islamique; féminismes noirs; génocide; histoire et politique; militance; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; études arabes; études décoloniales

Femmes autochtones et militantisme en ligne: usages de Facebook et Twitter pour contrer les violences sexuelles dans la foulee du scandale policier de Val-d'Or - Pilote, Anne-Marie; Hubner, Lena A. (Recherches Feministes, 2019)
Les auteures interrogent l’apport des médias socionumériques aux luttes des femmes autochtones du Québec. À la suite du scandale de Val-d’Or – qui a vu des agents de la Sûreté du Québec éclaboussés par des allégations d’agressions sexuelles envers des femmes des nations crie et anichinabée –, les chercheuses ont mené une observation ethnographique dans les comptes Facebook et Twitter des principales militantes et associations autochtones ayant investi les médias socionumériques pour dénoncer ces violences policières. Complétée par des entrevues, leur analyse montre que la variété des actions privilégiées en ligne donne une visibilité accrue aux luttes des femmes autochtones et favorise leur prise de parole. Ces actions se révèlent des moyens efficaces pour décoloniser l’ordre social patriarcal et forger un « espace de la cause des femmes autochtones ».
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; communication; cours; discipline; féminisme autochtone; militance; pol4105; premier cycle; périodes historiques; québec; racisme; régions géographiques; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; val-d'or; violences; violences policières; violences sexuelles

Walking With Our Sisters: une commemoration artistique pour le feminicide autochtone, en marche vers la decolonisation - Bruneau, Julie (Recherches Feministes, 2017)
In reaction to the indigenous femicide in Canada, and to the inaction of the canadian government, the victim's relatives and grassroots indigenous women groups created various memorials. The author focuses on the commemorative art installation Walking With Our Sisters, project of the Métis artist Christi Belcourt. Thus, the author led a field survey, to better understand if it was an empowering experience for the women participants. She will also question the definition of western feminism, in contrast with indigenous feminism.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; art contemporain; artistes autochtones; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; femmes* artistes; féminicide; féminisme autochtone; féminisme décolonial; histoire et politique; intersectionnalité; militance; mémoire; mémorial; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; thématiques; violences

Stitching through Silence: Walking With Our Sisters, Honoring the Missing and Murdered Aboriginal Women in Canada - Anderson, Stephanie G. (TEXTILE, 2016)
This article explores the complex relationship between processes of making, memory, healing, and social activism activated by Walking With Our Sisters, a large-scale commemorative installation intended to foster awareness for missing and murdered Indigenous women in Canada.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; art autochtone; art contemporain; artistes autochtones; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; féminicide; féminisme autochtone; histoire de l'art; histoire et politique; militance; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Idle No More: identité autochtone actuelle, solidarité et justice sociale : Entrevue avec Melissa Mollen Dupuis et Widia Larivière - Gentelet, Karine (Nouvelles pratiques sociales, 2014)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; environnement; féminisme autochtone; militance; pol4105; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; science politique et droit; thématiques

The winter we danced: voices from the past, the future, and the Idle No More movement - Kino-nda-niimi Collective (ARP Books, 2014)
"The Winter We Danced is a vivid collection of writing, poetry, lyrics, art and images from the many diverse voices that make up the past, present, and future of the Idle No More movement. Calling for pathways into healthy, just, equitable and sustainable communities while drawing on a wide-ranging body of narratives, journalism, editorials and creative pieces, this collection consolidates some of the most powerful, creative and insightful moments from the winter we danced and gestures towards next steps in an on-going movement for justice and Indigenous self-determination"
Section: 439 pages : illustrations (certaines en couleur) ; 22 cm
Keywords: 2000 à aujourd'hui; 2010-2019; DIG; amériques; approches et analyses; arts; canada; care; cours; créativité; discipline; féminisme autochtone; images; justice sociale; militance; musique; pol4105; poésie; premier cycle; périodes historiques; régions géographiques; santé; thématiques; études littéraires

Book Review: Making Space for Indigenous Feminism - Charron, Nadine (Gender and Development, 2008)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; critique de livre; féminisme autochtone; histoire et politique; militance; pol4105; pol5185; premier cycle; périodes historiques; régions géographiques; thématiques